2019
DOI: 10.1021/acs.orglett.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed [5 + 2] Oxidative Annulation of Cyclic Arylguanidines and Alkynes to 1,3-Benzodiazepines. A Striking Mechanistic Proposal from DFT

Abstract: The Supporting Information is available free of charge on the ACS Publications website. Detailed experimental procedures and compound characterization data (PDF) Computational details, cartesian coordinates, imaginary frequencies and absolute energies in hartrees for all optimized geometries (PDF) Crystallographic data for 5cd (CCDC: 1873638) (CIF) Crystallographic data for 5ia (CCDC: 1873637) (CIF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In 2019, a Rh(III)-catalyzed [5 + 2] oxidative annulation of cyclic arylguanidines and alkynes to 1,3benzodiazepines, using molecular oxygen as the terminal oxidant, was achieved by Sáa group (Scheme 50). [41] Intriguingly, when with partially cyclic arylguanidine substrates, a [5 + 1] oxidative annulation was observed. Mechanistic investigation including DFT calculation support that an eight-membered rhodacycle might be invovled in this transformation.…”
Section: Cà H Activation Of Amine and Imine Derivativesmentioning
confidence: 99%
“…In 2019, a Rh(III)-catalyzed [5 + 2] oxidative annulation of cyclic arylguanidines and alkynes to 1,3benzodiazepines, using molecular oxygen as the terminal oxidant, was achieved by Sáa group (Scheme 50). [41] Intriguingly, when with partially cyclic arylguanidine substrates, a [5 + 1] oxidative annulation was observed. Mechanistic investigation including DFT calculation support that an eight-membered rhodacycle might be invovled in this transformation.…”
Section: Cà H Activation Of Amine and Imine Derivativesmentioning
confidence: 99%
“…A Rh-catalyzed carboamination reaction of arylguanidines 36 and alkynes 2 for the quick synthesis of 1,3-benzodiazepines 37 was studied by Saá and co-workers ( Scheme 20 ). 31 In general, it was observed that use of molecular oxygen as oxidant was accompanied by better yields in comparison with the traditional oxidants like silver. Both aromatic and aliphatic alkynes were used in the reaction.…”
Section: Carboamination Of Alkynesmentioning
confidence: 99%
“…1,3-Benzodiazepines have been synthesized under Rh catalysis using nitrogenated substrates bearing X-Type (ureas) [54] and L-Type (guanidines) [55] DGs via (5 + 2) annulations ( Figure 7).…”
Section: 3-benzodiazepinesmentioning
confidence: 99%
“…Recently, Saá and co-workers reported the Rhcatalyzed (5 + 2) heteroannulation of cyclic arylguanidines 43 and alkynes 2 to give 1,3-benzodiazepines 44 (Scheme 17). [55] The use of O 2 (method B) as the sole oxidant in place of typical metal oxidants, like AgOAc (method A), clearly improves the efficiency of the oxidative annulation. The striking mechanism for this (5 + 2) annulation was supported by DFT calculations.…”
Section: 3-benzodiazepinesmentioning
confidence: 99%